Peranan Administrasi Pendidikan Terhadap Perkembangan Pendidikan Islam Di Ma'had Sasnasuksa (Sayap) Pattani Thailand Selatan - Lateh, Ridwan; , Drs. M. Yusron, M.Ag; , Dr. Ari Anshori, M.Ag (2017)
This study aims to determine the application of the system of educational administration and its influence on the development of Islamic education in Ma'hadSasnasuksa (Wing) Pattani, southern Thailand. In general, this study aims to identify and analyze the role of educational administration on the development of Islamic education in Ma'hadSasnasuksa (Wing) South Pattani Thailand, which is expected to contribute significantly to the development of educational administration and Islam in general. This research uses qualitative research methods, taking background in Pattani. Determination of the subjects in this study using a random sampling technique. Data collection methods used in this study were interviews, observation and documentation. Interview method is used to determine the administrative system of education and to evaluate the implementation process in the management or administration of education and its influence on the development of education in Islamic educational institutions in Ma'hadSasnasuksa (Wing), Pattani, South Thailand, Seeking documentation method to determine the school's history, geography, and evaluation related to educational administration school.